10p-8=-8(6p-5)+10(2+4p)

Simple and best practice solution for 10p-8=-8(6p-5)+10(2+4p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10p-8=-8(6p-5)+10(2+4p) equation:


10p-8=-8(6p-5)+10(2+4p)

We simplify the equation to the form, which is simple to understand
10p-8=-8(6p-5)+10(2+4p)

Reorder the terms in parentheses
10p-8=+(-48p+40)+10*(2+4p)

Remove unnecessary parentheses
+10p-8=-48p+40+10+*(+2+4p+)

Reorder the terms in parentheses
10p-8=-48p+40+(+20+40p)

Remove unnecessary parentheses
+10p-8=-48p+40+20+40p

We move all terms containing p to the left and all other terms to the right.
+10p+48p-40p=+40+20+8

We simplify left and right side of the equation.
+18p=+68

We divide both sides of the equation by 18 to get p.
p=3.7777777777778

See similar equations:

| x^3=1/27 | | x=5y+5+7y+6-11y-11 | | (11/4)-(6/5) | | 11/4-6/5 | | 1.2x=x+2 | | 8a-2,1/2=5,1/2 | | x=180+-1y+-1z | | a^3-27b^3= | | x^3-x^2-x+1= | | -3y(-4y)=32+(x+y) | | x=(1/4)2 | | x=2(1/2)(2) | | x=0(-1) | | 456x*5=17 | | x=0+(-1) | | 5=x(3-lnx) | | x=(1/2)(-1) | | x=-(-1) | | 3x*4=98 | | 2x^2+4y-3=0 | | p+5p-4=10 | | x=((1/4)(1/2)(-1)) | | 6k-13=4k+15 | | 5x=3x-lnx | | 5(x-3)=3(x+6) | | 3x+7/5=5 | | x=-(5/8)(-1/4) | | 3(x-2)-(4x-10)=-3 | | M/13=-3 | | M/3=10 | | 2(3x-7)+4(3x+2)=6(5x+9)+8 | | 5=30-25 |

Equations solver categories